Expression of fibroblast growth factor receptors during development and regression of the bovine corpus luteum - Guerra, D. M. [UNESP]; Giometti, I. C. [UNESP]; Price, C. A.; Andrade, P. B. [UNESP]; Castilho, A. C. [UNESP]; Machado, M. F.; Ripamonte, P. [UNESP]; Papa, P. C.; Buratini, J. [UNESP] (CSIRO Publishing, 2008)
There is evidence that fibroblast growth factors (FGFs) are involved in the regulation of growth and regression of the corpus luteum (CL). However, the expression pattern of most FGF receptors (FGFRs) during CL lifespan is still unknown. The objective of the present study was to determine the pattern of expression of 'B' and 'C' splice variants of FGFRs in the bovine CL. Bovine CL were collected from an abattoir and classed as corpora hemorrhagica (Stage I), developing (Stage II), developed (Stage III) or regressed (Stage IV) CL. Expression of FGFR mRNA was measured by semiquantitative reverse transcription-polymerase chain reaction and FGFR protein was localised by immunohistochemistry. Expression of mRNA encoding the 'B' and 'C' spliced forms of FGFR1 and FGFR2 was readily detectable in the bovine CL and was accompanied by protein localisation. FGFR1C and FGFR2C mRNA expression did not vary throughout CL lifespan, whereas FGFR1B was upregulated in the developed (Stage III) CL. FGFR3B, FGFR3C and FGFR4 expression was inconsistent in the bovine CL. The present data indicate that FGFR1 and FGFR2 splice variants are the main receptors for FGF action in the bovine CL.
Keywords: cattle